Differences in the achievement motivation in young football players and non-athletes - Milan Jelić (University of Novi Sad, Faculty of Sport and Physical Education, 2018)
There was lot of previous researches about achievement motivation, but also not lot of comparisons between young footballers and non-footballers. This article intend to improve psychological way of working with young sportmen and help to coaches how to approach in positive way to young person. The main objective of this research was to determine the differences in the level of achievement motivation at boys age 10-14 years (N=200) in relation with sport status, school success and economic characteristics who were divided into 2 subsamples: who are/or not engaged in football. In this study, for data collection the MOP2002 scale was used (Franceško, Mihić, Bala, 2002). For the purpose of data processing in this study were used methods of descriptive and multivariate statistics (t - test, canonical discriminant analysis, F-test). Application of canonical discriminant analysis which showed that the discriminating canonical correlation function of 0,39 (λ= 0.86; χ2 = 22.40; r = 0.00), which means there is a statistically significant difference regarding the structure of the achievement motivation. The results of the research indicate that engagement in football by an individual causes the higher level of the achievement motivation, with the most pronounced contribution by the component "persistence in achieving goals", and then "goals achievement as a source of satisfaction". Also, the results show that the economic status of the family didn't contribute to differences in achievement motivation of their children, and difference in the school success of the respondents is followed by level of its motivation.